Chronic idiopathic axonal polyneuropathy and vitamin B6: a controlled population‐based study. Issue 2 (June 2014) - Visser, Nora A.; Notermans, Nicolette C.; Degen, Lieveke A. R.; de Kruijk, Jelle R.; van den Berg, Leonard H.; Vrancken, Alexander F. J. E.
Abstract Vitamin B6 intoxication can result in a sensory ataxic neuropathy, but the association with a milder predominantly sensory or sensorimotor phenotype in chronic idiopathic axonal polyneuropathy (CIAP) remains unclear. A total of 381 patients with CIAP and 140 healthy controls were prospectively included. In a standardized fashion the use of vitamin B6 containing supplements and vitamin B6 levels were compared between patients and controls. On follow‐up, patients were questioned about cessation of supplement use and the impact on the symptoms of polyneuropathy. Vitamin B6 levels in patients (median: 99 nmol/l, range: 38–2, 967 nmol) were not significantly higher than in controls (median: 109 nmol/l, range: 41–2, 373 nmol/l, p = 0.58), nor were daily dose, cumulative dose or duration of supplement use. However, more patients (31%) than controls (22%) used vitamin B6 containing supplements (odds ratio [OR] 1.7, 95% confidence interval [CI] 1.0–2.7, p = 0.032). Follow‐up of patients confirming the cessation of supplements showed slow progression of symptoms in 64%, stabilization in 26%, and regression in 10%. On the basis of our prospective case–control study and review of the literature, an association between CIAP and vitamin B6 exposure or elevated vitamin B6 levels appears unlikely.